Religion beyond its Private Role in Modern Society. - Hofstee, Wim. (International Studies in Religion and Society, 2013)
The volume Religion beyond its Private Role in Modern Society aims at contributing to the debate on the distinction between public and private spheres with regard to the role of religion in modern societies. This issue which is inherent to many conceptions regarding social order, modernity, freedom of conscience, and the changing role and function of religion is discussed not only from a social scientific but also from a historical and philosophical point of view. The articles dwell on several aspects of the role of religion in different societies in modern times, and the overall theme is explored from the perspective of various religious traditions and groups, both institutional and non-institutional. It turns out that the distinction made is difficult to maintain.